The Effectiveness of Using Repetition Drill Technique with Duolingo Application to Improve Vocabulary at Seventh Graders of MTs Al-Huda Reban: Efektivitas Penggunaan Teknik Repetition Drill dengan Aplikasi Duolingo untuk Meningkatkan Kosakata pada Siswa Kelas Tujuh MTs Al-Huda Reban - Kurnia, Erika Dewi; Widyantoro, Arif (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Vocabulary is one of the elements to master, and this is important. Based on some difficulties in learning English, especially to improve vocabulary. Teachers must be able to find creative and effective ways to teach vocabulary to their students. This study aims to determine the efficacy of the repetition drill method by using Duolingo application to increase vocabulary in seventh grade in MTs Al-Huda Reban. This study employs a quantitative methodology. The study will employ an experimental design and involve two classes, each class consisting four meetings. One class studied English by using technique of repetition drill with Duolingo application and one class without this technique. It can be seen, the experimental class scored 80,54, whereas the controlled class scored 74,46. The two hypotheses are accepted (H1) and the null hypothesis (H0) is rejected (T-test result), as the significant value (2-tailed) 0,006 is less than alpha = 0,05. Based on the outcomes of the N-Gain computation, the average value of 55.0822 falls into the moderately effective category. Thus, it can be said that using the Duolingo application and the repetition drill approach is a useful way to increase vocabulary.